Evaluating Performance Impacts in Identity Management based on Keycloak and OpenID Connect - Bunn, Carlos D. S.; Miers, Charles C. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais Estendidos do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2024)
Using third-party identity providers (IdP) to allow authentication and authorization lets web developers add different IdPs easily. Centralized authentication/authorization services, such as the robust Keycloak framework, provide a reliable and straightforward solution for web developers, ensuring easy and efficient authentication and authorization management. However, Keycloak may introduce some latency and increase the payload of the system traffic. We analyze Keycloak employing OpenID Connect and solely OpenID Connect performance, focusing on identity and token delegation and characterizing their impacts and behavior.